Death risk among COVID-19 patients with diabetes mellitus - Dahlia Dahlia; Kurnia Dwi Artanti; Arief Hargono; Santi Martini; Nayla Mohamed Gomaa Nasr; Chung-Yi Li (Journal of Public Health in Africa, 2022)
Deaths from COVID-19 are increasing in patients with comorbidities. One of the most common comorbidities is diabetes mellitus. The researchers wanted to see how having diabetes affected the mortality rate of COVID-19 participants. This investigation is a case control observational analytical study. Different types of people, called “cases,” and “controls,” complete the research sample. Each group had 68 responders, for a grand total of 136. Medical records from COVID-19 patients treated at Airlangga University Hospital, Surabaya, between March 2020 and September 2021 serve as the study’s secondary data source. The purpose of this study’s data analysis is to calculate an odds ratio. Patients with COVID-19 with concomitant diabetes mellitus had an increased risk of death, and this risk increased with age, gender, and COVID-19 symptoms. In contrast, education, occupation, and laboratory results were not significantly related to mortality among COVID-19 individuals with concomitant diabetes mellitus (GDA status). The results of this study show that COVID-19 patients with concomitant diabetes mellitus are at a higher risk of death if they are over the age of 65, if they are male, and if they have severe symptoms.